The exergy of a phase shift: Ecosystem functioning loss in seagrass meadows of the Mediterranean Sea. (5th April 2015) - Montefalcone, Monica; Vassallo, Paolo; Gatti, Giulia; Parravicini, Valeriano; Paoli, Chiara; Morri, Carla; Bianchi, Carlo Nike
Abstract: Sustained functioning of ecosystems is predicted to depend upon the maintenance of their biodiversity, structure and integrity. The large consensus achieved in this regard, however, faces to the objective difficulty of finding appropriate metrics to measure ecosystem functioning. Here, we aim at evaluating functional consequence of the phase shift occurring in meadows of the Mediterranean seagrass Posidonia oceanica, a priority habitat that is undergoing regression in many coastal areas due to multiple human pressures. Structural degradation of the P. oceanica ecosystem, consequent to increasing coastal exploitation and climate change, may result in the progressive replacement of this seagrass by opportunistic macrophytes, either native or alien. Reviewing published information and our personal records, we measured changes in biological habitat provisioning, species richness and biomass associated to each of the alternative states characterizing the phase shift. Then, ecosystem functioning was assessed by computing the exergy associated to each state, exergy being a state variable that measures the ecosystem capacity to produce work. Phase shift was consistently shown to imply loss in habitat provision, species richness, and biomass; structural and compositional loss was parallelled by a reduction of exergy content, thus providing for the first time an objective and integrative measure of the loss of ecosystem functioning following the degradation of healthy seagrass meadows. Graphical abstract: Highlights: We evaluated functional consequence of the phase shift in Posidonia oceanica meadows. Degradation of meadows may result in their replacement by opportunistic macrophytes. Habitat provisioning, species richness and biomass reduced with the phase shift. Exergy was used as a synthetic and integrative index to measure changes in functioning.